Morphology Analysis Of Derivational Morphemes On Youtube BBC News - Putu Sarah Kaori Rahmadewi; Trisha Endah Setiawati; Ni Putu Raka Laksmi Arpin; Ni Made Diana Erfiani (Denpasar Institute, 2023)
Morphological process is a linguistic process that forms words. The process emphasized two main methods namely word formation and derivation. The derivation is used to form new words, by combining affixes. The derivational morpheme is added to the root of the word and generates new words and meanings. This research aims to explore derivational morphology in audio-visual mode. The data in this study was examined using morphological theories based on Fromkin’s theory. This research used a descriptive qualitative method by observing and taking note of the transcript of videos and continued by analysing the data; the data sources were taken from YouTube videos of BBC news. The result shows ten types of derivational morphology; nine can be found, and one new type of derivational morphology has been discovered. This study implies not only the detailed morphological process of affix analysis but also the grammatical categories of words and meanings